Leadership for Improving Teaching Quality: Analysis of School Practice in Northeast China - LI, YU; YAN, WENFAN; WEN, HENGFU (Advances in Social Sciences Research Journal, 2020)
Chinese education reform has vigorously advocated the improvement of teaching quality. School leaders determine the overall trend and effect of teaching quality improvement. Based on the TQM theory, Baldrige Quality Program Education Criteria for Performance Excellence framework and distributed leadership theory, we defined the concept of leadership for teaching quality. The purpose of this study is to provide new understanding of the current situation and problems of teaching quality in primary and secondary schools in the northeast of China. 908 educators from 54 primary and secondary schools participated in this study. Our findings indicated that there were significant differences among different gender, first degree, position, school level and school area. Implications for improving the leadership for teaching quality in primary and secondary schools from both internal and external perspectives were discussed.